c.2 IB - Roy, Shyamal (New Delhi, 2007)
This book is written for professional managers, both in public and private sectors, who have little or no background in Economics, but have to face, on a regular basis, the challenges posed by a rapidly changing macroeconomic policy environment. The book attempts to provide an understanding of how macroeconomic policies work and, in turn, how they impact the business environment. It adopts a uniquely practical approach to explain various aspects by deliberately avoiding jargon, diagrams and equations. Instead, a `story? mode has been in-built for easy grasp. Written by Prof Shyamal Roy, who has over two decades of teaching this subject in Executive Development Programmes, both at IIMB and outside, the book integrates theory and practice seamlessly. The book will also be useful for MBA students as it provides an exposure to Indian macroeconomic policy issues in an integrated fashion.